Provision of Emergency Maxillofacial Service During the COVID-19 Pandemic : A Collaborative Five Centre UK Study. Issue 6 (July 2020) - Blackhall, K.K.; Downie, I.P.; Ramchandani, P.; Kusanale, A.; Walsh, S.; Srinivasan, B.; Shields, H.; Brennan, P.A.; Singh, R.P.
Abstract: The global pandemic of Coronavirus disease (COVID-19) represents one of the greatest challenges to healthcare systems, and has forced medical specialties to rapidly adapt their approaches to patient care. Oral and Maxillofacial Surgery is considered particularly at risk of disease transmission due to aerosol generation during surgical interventions, patient proximity and operating environment. On day 2 (26th March, 2020) of when severe restrictions in population movement were instigated in the United Kingdom, we began a study to prospectively monitor the presentation and management of maxillofacial emergencies at five hospital trusts. Data was collected onto an online live database fed through a smartphone application. Of the total 529 patients over six weeks, 395 attended for face-to-face consultations and 134 patients received remote consultations via telephone or video link. There were 255 trauma related cases, 221 infection and 48 cases of postoperative complications. Most trauma cases were minor soft tissue injury related to slip, trip or fall at home. There were 44 cases of facial fractures with a tendency for conservative treatment. 19 cases were related to domestic violence or self-harm. Of the 216 dental related emergencies, 68% could have been managed in the primary care setting. A quarter of all emergency patients were satisfactorily managed by remote consultations. There was a significant change in the provision of emergency maxillofacial service during the pandemic lockdown. We discuss the study findings as well as the potential implications in relation to planning for possible further COVID- 19 spikes and future pandemics.